Characteristics and dynamics of cognitive impairment in patients with primary and recurrent cerebral ischemic hemispheric stroke - A. A. Kozyolkin; А. А. Kuznietsov; L. V. Novikova (Zaporožskij Medicinskij Žurnal)
Acute cerebrovascular disease is a global medical and social problem of the modern angioneurology, occupying leading positions in the structure of morbidity and mortality among adult population of the world. Ischemic stroke – is one of the most common pathology. Today this disease took out the world pandemic. More than 16 million new cases of cerebral infarction recorded in the world each year and it “kills” about 7 million of people.